2021
DOI: 10.1177/03635465211024964
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of Subsequent Hip Surgery Before Primary Hip Arthroscopy for Femoroacetabular Impingement Syndrome: A Machine Learning Analysis of Preoperative Risk Factors in Hip Preservation

Abstract: Background: The number of patients requiring reoperation has increased as the volume of hip arthroscopy for femoroacetabular impingement syndrome (FAIS) has increased. The factors most important in determining patients who are likely to require reoperation remain elusive. Purpose: To leverage machine learning to better characterize the complex relationship across various preoperative factors (patient characteristics, radiographic parameters, patient-reported outcome measures [PROMs]) for patients undergoing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Previous studies have analyzed risk factors of revision hip arthroscopy. Haeberle et al 21 used machine learning to identify higher BMI and a lower preoperative Hip Outcome Score-Activities of Daily Living subscale as key preoperative risk factors for revision. In addition, their model predicted the need for revision before the index hip arthroscopy with an accuracy of 76%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have analyzed risk factors of revision hip arthroscopy. Haeberle et al 21 used machine learning to identify higher BMI and a lower preoperative Hip Outcome Score-Activities of Daily Living subscale as key preoperative risk factors for revision. In addition, their model predicted the need for revision before the index hip arthroscopy with an accuracy of 76%.…”
Section: Discussionmentioning
confidence: 99%
“…49 Consequently, the number of patients requiring revision hip arthroscopy has also increased. 21 The most common causes of primary failed hip arthroscopy are labral retear and inaccurate cam morphology correction. 46 Moreover, the treatment of labral retears during revision hip arthroscopy often requires technically advanced procedures such as labral reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the performance of machine learning algorithms in predicting PROMs and the risk of reoperation. 10,17,22,29,30 Ramkumar et al 29,30 applied 7 machine learning models to predict whether patients would achieve the MCIDs of PROMs at 2 years after osteochondral allograft transplant, and the AUCs of the best-performing models ranged from 0.60 to 0.94. Haeberle et al 10 reported AUCs ranging from 0.62 to 0.80 for random forest models predicting the risk of subsequent hip surgeries before primary hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning has been introduced in clinical scenarios as an advanced approach to predict the outcomes of some surgical techniques, such as osteochondral transplant, 29,30 hip arthroscopic surgery, 10,16 and ACLR. 17,22,23 As a branch of artificial intelligence, machine learning is characterized by using well-documented historical data to predict future clinical outcomes using computational algorithms, thus combining related indicators and eliminating potential confounding factors to improve the accuracy of predictions.…”
mentioning
confidence: 99%
“…Most have focused on patient reported outcome, with Kunze et al analysing single-surgeon data to predict multiple post-operative endpoints based on different outcome measuring tools [19][20][21][22]. The prediction of subsequent surgery following hip arthroscopy has also been performed by Haeberle et al based on another single-surgeon database of over 3000 patients [11]. With their study, Haeberle et al achieved an AUC of 0.77 ± 0.08 for predicting a patient's risk of subsequent revision hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%